Components for use in energy storage or energy conversion devices and methods of manufacture thereof - Patents.com

JP2024518873A5Active Publication Date: 2025-02-28ILIKA TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023560764
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-29
Filing Date
2022-04-29
Publication Date
2025-02-28
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

Existing energy storage and conversion devices, such as batteries and fuel cells, face challenges in improving energy density and reliability, particularly in solid-state lithium-ion battery cells, which require robust electrodes that can withstand volume changes during charging and discharging.

Method used

A method involving the use of a slurry comprising ceramic particles is deposited onto a sheet with through-thickness openings, sintered at controlled temperatures, and optionally embedded with inorganic sintering aids to form electrodes, enhancing ion transport and mechanical robustness.

Benefits of technology

The method results in electrodes with improved porosity for liquid electrolyte penetration, reduced internal resistance, and increased energy density, while maintaining mechanical integrity and reducing the need for additional conductive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A method of manufacturing a component for an energy storage or energy conversion device includes providing a sheet having a plurality of thickness-wise openings, forming a slurry including particles of a ceramic material, depositing the slurry on the sheet having the plurality of thickness-wise openings, and sintering the slurry at a sintering temperature greater than 300°C and less than or equal to 900°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to components for use in energy storage or energy conversion devices, in particular for use in batteries, capacitors, fuel cells (including solid oxide fuel cells and polymer electrolyte fuel cells), photovoltaic devices, piezoelectric devices, or thermoelectric converters, and methods for their manufacture. [Background technology]

[0002] Energy storage or conversion devices, such as batteries, capacitors, fuel cells (including solid oxide fuel cells and polymer electrolyte fuel cells), photovoltaic devices, piezoelectric devices, or thermoelectric converters, are typically composed of components fabricated by sintering ceramic particles.

[0003] It is desirable to configure these components to improve certain aspects of performance, such as energy density and / or reliability.

[0004] For example, it is desirable to improve the performance of components in battery cells, such as solid-state lithium-ion battery cells.

[0005] A solid-state lithium-ion battery cell is a type of rechargeable battery cell that uses lithium ions (Li + ) moves from the negative electrode (anode) to the positive electrode (cathode) during discharge and back again during charging. The electrodes can each reversibly store lithium ions and are separated by a bulk solid electrolyte that allows ion transport.

[0006] Solid-state battery cells potentially offer several advantages over liquid electrolyte lithium-ion battery cells, such as increased energy density, increased power density, lower leakage current and / or reduced flammability, etc. Thus, solid-state battery cells are being considered for use in, for example, electric vehicles and consumer electronics.

[0007] Generally, solid-state battery cells include additional components such as current collectors, interfacial modifiers, and / or encapsulation or other protective elements. In some cases, the negative electrode is not present in the battery cell immediately after assembly of the cell, but instead is provided as a lithium anode that is formed during initial charging of the battery cell. Summary of the Invention [Problem to be solved by the invention]

[0008] In a first aspect, the present invention may provide a method of manufacturing a component for an energy storage or energy conversion device, the method comprising the steps of providing a sheet having a plurality of thickness-wise openings, forming a slurry including particles of a ceramic material, depositing the slurry on the sheet having the plurality of thickness-wise openings, and sintering the slurry at a sintering temperature greater than 300°C and less than or equal to 900°C.

[0009] The term ceramic refers to an inorganic, non-metallic material. The ceramic material may be selected from the group consisting of electrode active materials, electrolytes, piezoelectric materials, photovoltaic materials, and thermoelectric materials. For the avoidance of doubt, other materials may also be present in the slurry, for example particles of further ceramic materials.

[0010] The term sintering refers to the process of compacting a material provided in particulate form by applying heat, and optionally pressure, to bond the particles together, and as is well known to those skilled in the art, at least a portion of the material remains in a solid state throughout the sintering process.

[0011] "Sintering the slurry" refers to sintering the ceramic particles contained in the slurry. Optionally, the slurry may be subjected to a drying process prior to the sintering step, as known in the art, to evaporate at least a portion of the liquid phase present in the slurry. The drying process is typically carried out at a temperature below 200°C.

[0012] For the avoidance of doubt, the sintering temperature is the maximum temperature reached during the sintering step.

[0013] Typically, the component is an electrode.

[0014] In some cases, the component may be an electrode for a battery cell, such as a solid-state battery cell, and the ceramic material may be the electrode active material. In such cases, the slurry may optionally include particles of electrolyte material and / or other components.

[0015] In some cases, the component may be an electrode for a battery cell that includes a liquid electrolyte. In such cases, the electrodes of the battery cell may be held apart by a separator, such as a porous polymeric membrane. Meanwhile, the liquid electrolyte provides an ionically conductive medium that allows ion transport between, and possibly within, the electrodes. The sintered nature of the electrodes formed according to the methods of the present invention typically provides sufficient porosity to allow the infiltration of the liquid electrolyte into the electrode. This enhances ion transport within the battery and reduces internal resistance.

[0016] By depositing the slurry on a sheet having a plurality of through-thickness openings, the slurry may penetrate the sheet, so that the sheet is partially or fully embedded in the ceramic material. The presence of the partially or fully embedded sheet may help provide a more robust component. For example, the presence of the sheet may facilitate handling of the component. Furthermore, the penetration of the slurry into the sheet may help protect the sheet from any aggressive chemicals in the sintering atmosphere. If the component is an electrode for a battery cell and the ceramic material is the electrode active material, the presence of the sheet may help the electrode to withstand volume changes of the electrode during charging or discharging of the battery cell.

[0017] Typically, the sintering temperature is in the range of 400°C to 900°C. In some cases, the sintering temperature may be in the range of 500°C to 900°C. In some cases, the sintering temperature may be in the range of 600°C to 900°C. For example, the sintering temperature may be in the range of 600°C to 800°C or 600°C to 700°C. The sintering time may be 1 to 4 hours.

[0018] Typically, the ability to sinter the slurry at these sintering temperatures is achieved by including an inorganic sintering aid in the slurry. This form of sintering is sometimes referred to as liquid phase sintering. When present in the slurry, the inorganic sintering aid is provided by a ceramic material. Typically, the inorganic sintering aid is a ceramic material with a melting point of 900°C or less. In some cases, the inorganic sintering aid has a melting point of 850°C or less, e.g., 800°C or less or 750°C or less. In some cases, the inorganic sintering aid has a melting point of 700°C or less.

[0019] The melting point of the inorganic sintering aid may be measured by differential scanning calorimetry of the inorganic sintering aid when provided in bulk form.

[0020] In some cases (e.g., when the component is an electrode in a battery cell), the inorganic sintering aid may be 10 -10 Scm -1 In some cases, the ionically conductive material has an ionic conductivity of greater than 10 -9 Scm -1 In some cases, the ionically conductive material has an ionic conductivity of greater than 10 -8 Scm -1 In some cases, the ionically conductive material has an ionic conductivity of greater than 10 -7 Scm -1 In some cases, the ionically conductive material has an ionic conductivity of greater than 10 -6 Scm -1 The ionic conductivity is greater than 1.

[0021] The ionic conductivity of the sintering aid may be determined by analysis of the Nyquist plot obtained by electrochemical impedance spectroscopy at 25 °C of the ion-conductive material provided in bulk form.

[0022] The sintering aid may include a compound selected from the group consisting of oxides, carbonates (including Li2CO3), hydrides (including LiBH4), halides (including LiF, LiCl, LiBr, and LiI), silicates (including Li4SiO4), alkali metal hydroxides (such as LiOH), and mixtures thereof.

[0023] In some cases, the sintering aid may include a eutectic mixture of materials such as a LiOH-NaOH eutectic.

[0024] In some cases, the sintering aid may contain, as component elements, lithium, boron, and optionally carbon. For example, the sintering aid may include Li3BO3 (Li3BO3 has been shown to have an ionic conductivity of about 6.0×10 -8 S / cm and a melting point of about 800 °C).

[0025] In some cases, the sintering aid may include Li 3-x B 1-x C x O3 (0 < x < 1). For example, Li 2.2 C 0.8 B 0.2 O3 has been shown to have an ionic conductivity of about 8.0×10 -7 S / cm and a melting point of about 685 °C. Li 3-x B 1-x C x O3 (0.5 < x < 0.99) has been shown to have a melting point in the range of 680 °C to 750 °C.

[0026] When the component is an electrode for a battery cell and the ceramic material is an electrode active material, the amount of the sintering aid in the slurry is in the range of 1-50% by weight, preferably in the range of 2-30% by weight, based on the total amount of the electrode active material, electrolyte material, and sintering aid in the slurry.

[0027] When the component is an electrode for a battery cell and the ceramic material is the electrode active material, the sintering aid may be present in the slurry in the form of a coating that at least partially covers individual particles of the electrode active material and / or electrolyte material.

[0028] For the avoidance of doubt, the sintering aid is a solid at 25°C.

[0029] Generally, it is preferred to fix the sheet to a substrate (or support surface) prior to the step of depositing the slurry on the sheet. This helps to ensure that the sheet (as well as the surface of the component) is substantially planar. This is particularly preferred when the component is an electrode for a battery cell, as it helps to ensure that the thickness of the electrolyte separating the positive and negative electrodes in the battery is substantially constant, thus helping to reduce the risk of a short circuit between the two electrodes.

[0030] Typically, the sheet is secured to the substrate using a polymer-based adhesive, such as a sticky tape.

[0031] In some cases, the slurry is deposited on the sheet by a sheet-to-sheet process. The sheet-to-sheet process is usually an intermittent process and may include processes such as tape casting, screen printing, etc. In other cases, the deposition process may be a roll-to-roll process. The roll-to-roll process is typically a continuous process and may include processes such as comma bar, K-bar, doctor blade, slot die, flexographic, gravure, intaglio, and lithographic coating. Detailed descriptions and requirements of these processes are disclosed in "The Printing Ink Manual" RH Leach and RJ Pierce eds. 5thed 1993 (ISBN 0 9448905 81 6), which is incorporated herein by reference.

[0032] Generally, the sheet having a plurality of through-thickness openings is an electronically conductive sheet. For example, the sheet may comprise a metal or alloy. In some cases, the sheet may comprise iron or steel (including stainless steel, i.e., steel containing at least 10% chromium by weight). For example, the sheet may comprise stainless steel containing chromium, nickel, and molybdenum. In some cases, the stainless steel may comprise 15-20% chromium by weight, 10-15% nickel by weight, and 1-5% molybdenum by weight. In some cases, the stainless steel may have a low carbon content, i.e., 0.05% or less by weight, in some cases 0.03% or less by weight.

[0033] When the component is an electrode for a battery cell and the ceramic material is the electrode active material, such a conductive sheet may replace the current collector of the electrode and / or reduce or eliminate the need to include additional conductive components in the slurry. This may increase the energy density of the battery cell. Furthermore, because the sheet is partially or completely embedded in the electrode active material, the interfacial contact area between the electrode active material and the sheet may be increased compared to a configuration in which the current collector is provided as a separate layer with a planar interface with the electrode. This may reduce the internal resistance of the battery cell.

[0034] In such a case, the amount of the additional electronically conductive component in the slurry may be less than 10% by volume relative to the total volume of the particles of the electrode active material. Preferably, the amount of the additional electronically conductive component in the slurry is less than 5% by volume relative to the total volume of the particles of the electrode active material. More preferably, the amount of the additional electronically conductive component in the slurry is less than 2% by volume relative to the total volume of the particles of the electrode active material. Even more preferably, the amount of the additional electronically conductive component in the slurry may be less than 1% by volume relative to the total volume of the particles of the electrode active material.

[0035] If an additional electronically conductive component is present, it typically has a thermal conductivity of at least 10 as measured by DC decay measurements at 25° C. -4 Scm -1In certain embodiments, the electronic conductivity of the additional electronically conductive component is at least 10 -3 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 10 -2 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 10 -1 Scm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 1 S cm -1 In certain embodiments, the electronic conductivity of the additional electronically conductive component may be at least 10 S cm -1 It may be.

[0036] The electronically conductive component, if present, may typically comprise a material selected from the group consisting of carbon black, acetylene black, activated carbon, carbon nanotubes, carbon fibers, titanium nitride, indium tin oxide, antimony tin oxide, vanadium pentoxide, non-stoichiometric molybdenum nitride, aluminum doped zinc oxide, tantalum carbide, and mixtures thereof. Alternatively, the electronically conductive component may be provided by a metal powder.

[0037] Generally, a sheet having a plurality of openings through the thickness is provided by a woven mesh. Generally, woven meshes including metal or metal alloy strands are commercially available in a variety of types, each having a different number of strands per unit distance measured perpendicular to the strands. Meshes having a small number of strands per unit distance tend to have a large individual strand thickness, which tends to result in a large mesh weight per unit area. Therefore, it is generally preferable to avoid meshes having a very small number of strands per unit distance.

[0038] Typically, woven mesh has 5-500 strands per cm, measured perpendicular to the strands. In some cases, woven mesh has 30-250 strands per cm, measured perpendicular to the strands. In other cases, woven mesh has 30-100 strands per cm, measured perpendicular to the strands.

[0039] The weave of the mesh is not particularly limited. Typically, the weave is a plain weave, with each strand passing alternately over and under strands oriented transversely to it.

[0040] Generally, the openings in the thickness direction of the sheet have a width in the range of 10 to 1000 μm. For example, the openings may have a width in the range of 10 to 200 μm. In some cases, the openings may have a width in the range of 50 to 200 μm.

[0041] The width of the aperture is the smaller dimension of the aperture in the plane of the sheet. Typically, the apertures have a square shape. In such cases, the width of the aperture corresponds to the length of one side of the square. In some cases, the apertures may be circular. In such cases, the width of the aperture corresponds to the diameter of the circle. In some cases, the apertures may have a rectangular shape. In such cases, the width of the aperture corresponds to the length of the short side of the rectangle.

[0042] Generally, the multiple openings are arranged in a regular array.

[0043] In some cases, a sheet having a plurality of through-thickness openings may be provided by a sheet having a plurality of through-thickness perforations, such as a grid.

[0044] For the avoidance of doubt, the term "thickness opening" may be defined as an opening that extends directly laterally across the sheet from a first surface of the sheet to an opposing second surface of the sheet.

[0045] When the component is an electrode for a battery cell and the ceramic material is the electrode active material, the choice of electrode active material is not particularly limited.

[0046] Typically, when the electrode is intended for use as an anode in a battery cell, the electrode active material is selected from the group consisting of elements such as lithium, silicon, carbon, tin, magnesium, aluminum, titanium, boron, iron, and combinations thereof. Alternatively, the electrode active material may include phosphates, nitrides, and / or oxides of these elements. Specific examples of compounds that can be used in the anode include lithium titanium oxide (Li4Ti5O 12 or Li2TiO3) and SnO2.

[0047] Conversely, typically, if the electrode is intended to be used as a cathode in a battery cell, The electrode active material is a compound that includes a cation of lithium and one or more transition metals, and an anion selected from the group consisting of an oxide anion, a sulfide anion, and a polyanion. Suitable polyanions include, but are not limited to, phosphate, PO4F, and SO4F.

[0048] For example, if the electrode is intended to be used as a cathode in a battery cell, the electrode active material may be lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2), lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), lithium manganese nickel oxide (LiMn 1.5 Ni 0.5 O4), lithium cobalt phosphate (LiCoPO4), lithium nickel cobalt manganese oxide (LiNi x Co y Mn zO2, x>0, y>0, z>0, x+y+z=1), vanadium oxide (VO5), LiVOPO4, Li3V2(PO4)3, and combinations thereof. For example, where the electrode is intended for use as a cathode in a battery cell, metal chalcogenides such as TiS3, NbSe3, LiTiS2, and combinations thereof may also provide suitable electrode active materials.

[0049] A description of suitable electrode active materials for both the anode and cathode may be found in Nitta et al. Materials Today, 2015, 18, 252-264, which is incorporated herein by reference.

[0050] Typically, the particles of the ceramic material have a d50 size in the range of 10 nm to 50 μm, as measured using laser diffraction of a dispersion of the particles according to ISO 13320:2020. For example, the particles of the ceramic material may have a d50 size in the range of 100 nm to 40 μm. In some cases, the particles of the ceramic material may have a d50 size in the range of 1-40 μm. In some cases, the particles of the ceramic material may have a d50 size in the range of 2-20 μm.

[0051] When the component is an electrode for a battery cell and the ceramic material is the electrode active material, in some cases, particles of an electrolyte material are present in the slurry. This may help to increase the ionic conductivity of the resulting electrode. The selection of the electrolyte material is not particularly limited. Typically, the electrolyte material is a lithium-containing electrolyte material. For example, the electrolyte material may be a lithium garnet electrolyte material. In some cases, the electrolyte material may be a lithium-containing oxide material. For example, the electrolyte material may be selected from the group consisting of lithium lanthanum zirconium oxide (LLZO) and cation-doped LLZO, and the cation dopant may be selected from the group consisting of tantalum, barium, yttrium, zinc, niobium, aluminum, germanium, strontium, gallium, titanium, and combinations thereof.

[0052] Typically, the particles of the electrolyte material have a greater ionic conductivity than the inorganic sintering aid. Generally, the particles of the electrolyte material have a melting point above 900°C.

[0053] In general, the particle size of the electrolyte material is smaller than the particle size of the electrode active material.

[0054] Typically the slurry formed in the method according to the first aspect of the invention also comprises an organic binder phase and a solvent for the organic binder phase.

[0055] The selection of the organic binder is not particularly limited, so long as it serves the function of providing the slurry with some mechanical strength after deposition and before sintering. For example, the organic binder may be selected from the group consisting of vinyl polymers (including polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl butanol, polyvinyl acetate, and vinyl chloride acetate), acrylic polymers (including polyacrylic acid esters, polymethyl methacrylate, polyethyl methacrylate), cellulose binders (including ethyl cellulose, methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, nitrocellulose, cellulose acetate butyrate), polypropylene carbonate, polyethylene carbonate, and polyethylene oxide. Preferably, the organic binder is selected from the group consisting of ethyl cellulose, polypropylene carbonate, polyethylene carbonate, polyvinyl alcohol, polyethylene oxide, and carboxymethyl cellulose.

[0056] Generally, the amount of organic binder in the slurry is in the range of 1-20% by weight, preferably in the range of 5-15% by weight, based on the total amount of solid materials in the slurry.

[0057] The solvent is typically an organic solvent, such as terpineol, benzyl alcohol, toluene, xylene, ethanol, methanol, methyl ethyl ketone, ethylene glycol ethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol ethyl isobutyl ether, neopentyl glycol monoisobutyrate, diethylene glycol monobutyl ether, ethylene glycol ether, diethylene glycol monohexyl ether, propylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, butyl carbitol acetate, acetic acid 2-butoxyethyl ester, acetic acid 2-ethoxyethyl ester, acetic acid 2-methoxyethyl ester, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Texanol TM ), C10-C40 alcohols, ethyl lactate, dipropylene glycol monomethyl ether, 2 ethylhexanoic acid, trimethylhexanoic acid, tetrahydrofurfuryl alcohol, furfuryl alcohol, 2-(benzyloxy)ethanol, 2-phenoxyethyl alcohol, 2-(methoxymethoxy)ethanol, triethylene glycol monomethyl ether, triethylene glycol, diethylene glycol monobutyl acetate, butyl carbitol acetate, phenylium esters, phenoxy ethylhexoate, glycol monomethyl phenyl ether, diethylene glycol phenyl ether, glycol monomethyl benzyl ether, diethylene glycol single benzyl ether, propylene glycol phenyl ether, benzyl glycol, phenylacetic acid methyl ester, phenylacetic acid ethyl ester, ethyl benzoate, methyl benzoate, gamma-butyrolactone, dimethyl sulfoxide (DMSO), N-methylpyrrolidone, N-methylacetamide, ethanamide, N-dimethylformamide, N-methylformamide, methanamide, and combinations thereof.

[0058] The slurry may further include a dispersant and / or a plasticizer.

[0059] Typically, the slurry is deposited on the sheet in an amount such that the thickness of the sintered component is greater than the thickness of the sheet. That is, the amount of slurry that penetrates the openings in the sheet is typically only a portion of the total amount of slurry deposited. In general, the slurry is deposited on the sheet in an amount such that the thickness of the sintered component is at least 30% greater than the thickness of the sheet. In some cases, the thickness of the sintered component is at least 50% greater than the thickness of the sheet. In some cases, the thickness of the sintered component is at least 80% greater than the thickness of the sheet.

[0060] In some cases, the sheet is not directly fixed to the substrate, for example by a polymer-based adhesive, but is indirectly fixed to the substrate (or support surface) by a mask. In such a case, the method further comprises, prior to depositing the slurry on the sheet, providing a support surface and a mask, the mask comprising at least one window, positioning the sheet between the support surface and the mask such that a first side of the sheet faces the mask, a first portion of the sheet being shielded by the mask and a second portion of the sheet being exposed through the window in the mask, and reversibly fixing the mask to the support surface.

[0061] Generally, the mask is reversibly fixed to the support surface using magnetic means. That is, typically, one of the mask and the support surface is magnetized and the other of the mask and the support surface comprises a magnetic material. In a preferred case, the support surface is magnetized and the mask comprises a magnetic material, for example ferromagnetic steel. It is believed that this allows a thin mask to be provided, which may facilitate the process of depositing the slurry on the sheet.

[0062] In some cases, the mask may be reversibly secured to the support surface using one or more mechanical fasteners, however this is less preferred as it is believed that the mechanical fasteners may interfere with the deposition of the slurry.

[0063] In some cases, the method may further include the steps between depositing the slurry and sintering the slurry: removing the mask from the support surface, flipping the sheet so that the first side of the sheet faces the support surface, placing a mask over the sheet and reversibly securing the mask to the support surface, and depositing an additional amount of the slurry including particles of ceramic material onto a portion of a second side of the sheet opposite the first side of the sheet.

[0064] Typically, prior to the step of inverting the sheet, the deposited slurry is dried to evaporate at least a portion of the liquid phase of the slurry.

[0065] Preferably, the slurry is deposited to a first thickness and an additional amount of the slurry is deposited to a second thickness, the ratio of the first thickness to the second thickness being between 0.5-2. The sheet may thus be disposed substantially in the central plane of the component. This may be particularly advantageous where the sheet is electrically conductive and acts as a current collector.

[0066] In some cases, the method may include additional steps between depositing the slurry on the sheet indirectly secured to the support surface by the mask such that the first portion of the sheet is shielded by the mask and sintering the slurry, and may further include removing the mask from the support surface, bending the sheet such that a portion of the first portion of the sheet overlaps the deposited slurry, reversibly securing the mask to the support surface such that a portion of the first portion of the sheet is exposed through a window in the mask, and depositing a further amount of the slurry including particles of ceramic material onto the exposed portion of the first portion of the sheet.

[0067] In some cases, the step of bending the sheet to reversibly secure the mask to the support surface, followed by the step of obscuring a further portion of the first portion of the sheet by the mask, may further comprise the following steps between the steps of depositing the further amount of slurry and sintering the slurry: removing the mask from the support surface, bending the sheet such that the further portion of the first portion of the sheet at least partially overlaps the further amount of slurry, reversibly securing the mask to the support surface such that the further portion of the first portion of the sheet is at least partially exposed through a window in the mask, and depositing a further amount of the slurry comprising particles of ceramic material onto the exposed portion of the further portion of the first portion of the sheet.

[0068] These optional method steps may provide a sheet that is folded one or more times within the component, which may be particularly advantageous if the sheet is conductive and acts as a current collector, as this may facilitate electronic conduction within the bulk volume of the component.

[0069] Another approach to providing a sheet that can be folded one or more times within a component may include the following steps after depositing the slurry on a sheet having a plurality of thicknesswise openings and before sintering: folding the sheet such that a first portion of the sheet overlies a second portion of the sheet, and both the first and second portions of the sheet are located within the area of ​​the sheet where the slurry was deposited. Typically, before folding the sheet, the deposited slurry is dried to evaporate at least a portion of the liquid phase of the slurry. Typically, after folding the sheet, but before or during sintering the deposited slurry, pressure is applied in the thickness direction of the first and second portions of the sheet.

[0070] In a second aspect, the present invention may provide a method for manufacturing a battery cell comprising the steps of: manufacturing a component according to the method of the first aspect of the present invention, the component being an electrode and the ceramic material being the electrode active material, fixing the electrode to a substrate, and depositing a further battery layer on the electrode.

[0071] The step of fixing the electrode to the substrate may be carried out using a polymer-based adhesive as described in relation to the first aspect of the invention, although sintered electrodes are typically sufficiently rigid that spot welding can be used for this step instead of a polymer-based adhesive.

[0072] Typically, the battery cells are solid-state battery cells.

[0073] In a third aspect, the present invention may provide a component for use in an energy storage or energy conversion device, the component being obtained or obtainable through a method according to the first aspect of the invention.

[0074] Typically, the component includes a sintered ceramic inclusion having a sheet partially or completely embedded therein that has a plurality of through-thickness openings.

[0075] In some cases, the component is an electrode of a battery cell. In such cases, the electrode may have a thickness in the range of 70 to 1000 μm. In some cases, the component is an electrode of a solid-state battery cell.

[0076] In a fourth aspect, the invention may provide a component for use in an energy storage or energy conversion device, the component comprising a first portion and a second portion, the first portion comprising particles of a ceramic material and the second portion provided by a sheet having a plurality of through-thickness openings and at least partially embedded in the first portion.

[0077] The term ceramic refers to an inorganic, non-metallic material. The ceramic material may be selected from the group consisting of electrode active materials, electrolytes, piezoelectric materials, photovoltaic materials, and thermoelectric materials. For the avoidance of doubt, other materials may also be present in the first portion, for example particles of a further ceramic material. The second portion may be partially or wholly embedded in the first portion.

[0078] Generally, the thickness of the component is greater than the thickness of the sheet. For example, the thickness of the component may be at least 30% greater than the thickness of the sheet. In some cases, the thickness of the component is at least 50% greater than the thickness of the sheet. In some cases, the thickness of the component is at least 80% greater than the thickness of the sheet.

[0079] Generally, particles of the ceramic material are bonded to provide a self-supporting network. In effect, the first portion may be provided by a sintered ceramic inclusion.

[0080] Typically, the components are electrodes.

[0081] In some cases, the component is an electrode for a battery cell, such as a solid-state battery cell, and the ceramic material is the electrode active material. In such cases, the electrode may further include particles of an electrolyte material and / or other components. The electrode for the battery cell may have a thickness in the range of 70 to 1000 μm.

[0082] Typically, the first portion comprises a sintering aid as described in relation to the first aspect of the invention. When the component is an electrode for a battery cell and the ceramic material is the electrode active material, the amount of sintering aid in the electrode is typically in the range of 1-50 wt.%, preferably in the range of 2-30 wt.%, based on the total amount of electrode active material, electrolyte material and sintering aid. In such cases, the sintering aid may be present in the form of a coating that at least partially covers individual particles of the electrode active material and / or electrolyte material.

[0083] A sheet having a plurality of thickness-wise openings may have one or more of the optional features of the corresponding sheet described in relation to the first aspect of the invention.

[0084] If the sheet is a conductive sheet and the component is an electrode for a battery cell, the need for including an additional electronically conductive component in the first portion of the electrode may be reduced or eliminated. If such an additional electronically conductive component is present, the additional electronically conductive component may have one or more of any of the characteristics described in relation to the corresponding component of the first aspect of the invention and / or may be present in an amount described in relation to the corresponding component of the first aspect of the invention.

[0085] Where the component is an electrode for a battery cell and the ceramic material is an electrode active material, the particles of the electrode active material may have one or more of any of the characteristics of the corresponding particles described in relation to the first aspect of the invention. Where the first part of the electrode further comprises particles of electrolyte material, these may have one or more of any of the characteristics of the corresponding particles described in relation to the first aspect of the invention.

[0086] In a fifth aspect, the present invention may provide an energy storage or energy conversion device comprising a component according to the third or fourth aspect of the invention. The device may be selected from the group consisting of a battery, a capacitor, a fuel cell (including solid oxide fuel cells and polymer electrolyte fuel cells), a photovoltaic device, a piezoelectric device, and a thermoelectric converter.

[0087] In a sixth aspect, the present invention may provide a solid-state battery cell comprising a component according to the third or fourth aspect of the present invention, wherein the component is an electrode, and the battery cell further comprises an electrolyte layer disposed on a surface of the electrode. [Brief description of the drawings]

[0088] The invention will now be described by way of example with reference to the following figures: [Figure 1a] 1 shows scanning electron micrographs of two faces (top and bottom) of the sintered cathode of Example 1. [Figure 1b] 1 shows scanning electron micrographs of two faces (top and bottom) of the sintered cathode of Example 1. [Diagram 2] 1 shows a graph of current versus time for the sintered cathode of Example 2. The current is normalized with respect to the first reading taken. [Diagram 3] 1 shows a graph of current versus time for the sintered cathode of Example 3. The current is normalized with respect to the first reading taken. [Figure 4] 1 shows a graph of current versus time for a comparative sintered cathode, where the current is normalized with respect to the first reading taken. [Diagram 5] 1 shows a schematic plan view of an apparatus for use in a method according to one example of the present invention. [Figure 6] 4 shows a schematic cross-sectional view of a component according to a first embodiment of a fourth aspect of the present invention. [Figure 7a] FIG. 1 shows a schematic cross-sectional view of a component according to a second embodiment of the fourth aspect of the present invention. [Figure 7b] FIG. 7b shows a schematic plan view of a mesh provided on the components of FIG. 7a prior to assembly of the components; [Figure 8] 4 shows a schematic cross-sectional view of a component according to a third embodiment of the fourth aspect of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0089] [Preparing the cathode] A slurry was prepared from the ingredients listed in Table 1. [Table 1]

[0090] The NMC cathode active material has the chemical formula LiNi 0.33 Mn 0.33 Co 0.33 Had O2. The LLZTO electrolyte has the chemical formula Li 6.4 La3Zr 1.4 Ta0.6 O 12 had the following characteristics: The LCBO sintering aid has the chemical formula Li 2.3 C 0.7 B 0.3 O3 and was prepared by heating a mixture of 10 g Li2CO3 and 5 g Li3BO3 at 650 °C for 12 h in air.

[0091] The woven metal mesh was attached to a stationary substrate using adhesive tape. The slurry was then cast onto the metal mesh using a screen printing process and allowed to dry. A total of 4-6 layers of the slurry were cast before drying.

[0092] The samples were sintered in argon in a Carbolite GSM1100 furnace.

[0093] Impedance measurements were performed on the sintered samples by sputtering 100 nm thick, 5 mm diameter circular Au contacts onto the top surface of the samples using a Leica sputter coater, and the impedance was then measured with a Solartron impedance analyzer.

[0094] The electronic conductivity of the electrode was measured by applying a constant voltage of 1 V and measuring the current for 1 h. The current was measured using a Keithley Source Meter.

[0095] Further details of the examples are provided in Table 2. [Table 2]

[0096] Figures 1a and 1b show SEM images of Example 1. They show that the cathode slurry penetrated the mesh and formed a homogenous and dense film with controlled thickness.

[0097] Figures 2 and 3 show that a constant current can be maintained across the sintered cathode, meaning no DC current decay is observed, indicating that an electronic conduction network is established.

[0098] [Comparative Example] Comparative examples were prepared in which the slurries in Table 1 were cast onto stainless steel foil (i.e., a sheet that did not contain multiple through-thickness openings). A total of two layers of the slurry were cast, and the samples were dried and sintered. The sintered specimens were 40 μm thick.

[0099] FIG. 4 shows that, even though the thickness of the electrode is less than half that of Examples 1 to 3, when no electronically conductive component is present in the slurry, significant DC current decay is observed.

[0100] [Preparing the battery cells] The cathode slurry was prepared as described above and cast onto a woven mesh of mesh size 200 and allowed to dry.

[0101] As mentioned above, the woven mesh was secured to a stationary substrate using adhesive tape prior to deposition of the cathode slurry.

[0102] An electrolyte slurry was then prepared from the LLZTO and LCBO particles, binder phase, and solvent, poured onto the cathode layer, and dried.

[0103] For the cathode layer, the two poured and dried layers were sintered using the same sintering conditions as those described above.

[0104] The sintering process burned away the adhesive tape used to secure the woven mesh, so after sintering, the cathode and electrolyte stack were fixed to the stationary substrate by spot welding.

[0105] A slurry containing silicon particles was then deposited onto the electrolyte layer and dried to provide a battery cell.

[0106] [Example 4] Referring to Figure 5, an apparatus 10 for preparing a component such as a cathode for a battery cell is shown. The apparatus includes a support surface (not shown), typically provided by a steel plate. A mask 12 is placed on the support surface. The mask 12 includes a window 14.

[0107] To prepare the component, a mesh 16, such as one of the meshes described in Table 2, is placed between the mask 12 and a support surface, with a first side of the mesh 16 facing the mask 12 and a second side of the mesh 16 facing the support surface. A first portion of the mesh 16 is exposed through the window 14 in the mask 12, while a second portion of the mesh is shielded by the mask.

[0108] The mask 12 is reversibly secured to the support surface by magnetic means, for example, a steel plate of the support surface may be magnetized and the mask 12 may comprise a ferromagnetic material, such as ferromagnetic stainless steel.

[0109] A predetermined amount of slurry, such as those set forth in Table 1, is deposited onto the mask 12 by tape casting or screen printing, penetrating the portions of the mesh 16 exposed through the mask windows 14. This first layer of slurry is then dried, for example, on a belt dryer.

[0110] Mask 12 is then removed from the support surface and mesh 16 is turned over so that a first side of the mesh faces the support surface. Mask 12 is then reversibly secured to the support surface such that windows 14 coincide with the portions of mesh 16 that have been saturated with the slurry. A second layer of slurry is then deposited on mask 12 to cover the portions of mesh 16 exposed through windows 14.

[0111] The two slurry layers are dried and sintered. The mesh 16 is then trimmed to remove much of the slurry-free portion, but leaving a mesh tab protruding from the slurry layer. The resulting component 18 is shown in FIG. 6, showing the two sintered slurry layers 20, 22 located on opposite sides of the trimmed mesh 16a. The mesh tab 16b allows an external electrical connection to be provided to the mesh. The thicknesses of the two sintered slurry layers 20, 22 are substantially equal.

[0112] [Example 5] Referring to Figure 7a, a component 40 suitable for a battery cell cathode includes a sintered part 42 containing particles of electrode active material and a mesh 44 embedded in the sintered part. Figure 7b shows mesh 44 of component 40 prior to fabrication.

[0113] The mesh 44 has a first portion 46 and a second portion 50 connected by a connecting portion 48. The first portion 46 and the second portion 50 of the mesh may have the characteristics of one of the meshes set forth in Table 2. The connecting portion of the mesh includes large through-thickness openings 49 that span multiple strands of the mesh to reduce the weight of the mesh.

[0114] Component 40 is prepared by depositing a first layer of slurry onto a first portion 46 of the mesh (the slurry may correspond to a slurry described in Table 1). During deposition of the slurry, the mesh is secured between a mask and a support surface, as described in connection with Example 4, to ensure that the mesh remains flat and that the slurry is deposited only on the first portion of the mesh.

[0115] The mask is then removed from the mesh and the mesh is bent at connecting portion 48 so that second portion 50 overlies the first layer of slurry. The resulting assembly is placed between the mask and a support surface as described with respect to Example 4, with the mesh maintained in its bent shape and the second portion 50 of the mesh exposed through the window in the mask. A second layer of slurry is then deposited on the second portion 50 of the mesh.

[0116] [Example 6] Referring to FIG. 8, a component 60 suitable for a battery cell cathode includes a sintered part 62 containing particles of electrode active material and a mesh 64 embedded in the sintered part.

[0117] The mesh 64 comprises a first portion 66, a second portion 70, and a third portion 74 aligned with one another and displaced relative to one another in the thickness direction of the component. The first portion 66 and the second portion 70 are connected by a first connecting portion 68, and the second portion 70 and the third portion 74 are connected by a second connecting portion 72. [Explanation of symbols]

[0118] 10 equipment 12. Mask 14. Windows 16 Mesh 16a Trimmed mesh 16b Mesh tab 18 Components 20 Sintering slurry layer 22 Sintering slurry layer 40 Components 42 Sintered parts 44 Mesh 46 First Part 48 Connecting part 49 Opening 50 Second Part 60 Components 62 Sintered parts 64 Mesh 66 First Part 68 First connecting part 70 Second Part 72 Second connecting part 74 Third Part

Claims

1. 1. A method of manufacturing a component for an energy storage or energy conversion device, comprising: Providing a sheet having a plurality of through-thickness openings; forming a slurry including particles of a ceramic material; depositing the slurry onto the sheet having the plurality of through-thickness openings; sintering the slurry at a sintering temperature greater than 300° C. and less than or equal to 900° C.; A method comprising:

2. The ceramic material is Selected from the group consisting of electrode active materials, electrolytes, piezoelectric materials, photovoltaic materials, and thermoelectric materials; The method of claim 1.

3. The component is an electrode for a battery cell, in particular a solid-state battery cell, and the ceramic material is an electrode active material; The method of claim 2.

4. The slurry further comprises an inorganic sintering aid; The inorganic sintering aid is 10 -10 S.C.M. -1 Provided by an ionically conductive material having a greater ionic conductivity and a melting point of 900° C. or less; The method according to claim 3.

5. The inorganic sintering aid contains lithium, boron, and optionally carbon as constituent elements; The method according to claim 4.

6. The inorganic sintering aid is Li 3 B.O. 3 and Li 3?x B 1?x C x O 3 where 0<x<1; The method according to claim 5.

7. Prior to the step of depositing the slurry on the sheet, further comprising the step of securing the sheet to a substrate. The method of claim 1.

8. The sheet is secured to the substrate by a polymer-based adhesive. The method of claim 7.

9. Prior to the step of depositing the slurry on the sheet, providing a support surface and a mask, said mask comprising at least one window; placing the sheet between the support surface and the mask such that a first side of the sheet faces the mask, a first portion of the sheet being obscured by the mask and a second portion of the sheet being exposed through a window in the mask; reversibly securing the mask to the support surface; The method of claim 1 further comprising:

10. The mask is reversibly secured to the support surface using magnetic means.

10. The method of claim 9.

11. one of the mask and the support surface is magnetized, and the other of the mask and the support surface comprises a magnetic material; The method of claim 10.

12. Between the steps of depositing the slurry and sintering the slurry, removing the mask from the support surface; turning the sheet over so that the first side of the sheet faces the support surface; placing the mask on the sheet and reversibly securing the mask to the support surface; depositing an additional amount of a slurry including particles of the ceramic material onto a portion of a second surface of the sheet opposite the first surface of the sheet; The method of claim 9 further comprising:

13. the slurry is deposited to a first thickness and the additional amount of slurry is deposited to a second thickness, a ratio of the first thickness to the second thickness being between 0.5 and 2; The method of claim 12.

14. Between the steps of depositing the slurry and sintering the slurry, removing the mask from the support surface; bending the sheet such that a portion of the first portion of the sheet overlies the deposited slurry; reversibly securing the mask to the support surface such that a portion of the first portion of the sheet is exposed through the window in the mask; depositing an additional amount of a slurry including particles of the ceramic material onto the exposed portion of the first portion of the sheet; The method of claim 9 further comprising:

15. After the step of bending the sheet to reversibly secure the mask to the support surface, the step of obscuring a further portion of the first portion of the sheet with a mask comprises: Between the steps of depositing the further amount of slurry and sintering the slurry, removing the mask from the support surface; bending the sheet such that the additional portion of the first portion of the sheet at least partially overlies the additional quantity of slurry; reversibly securing the mask to the support surface such that the further portion of the first portion of the sheet is at least partially exposed through the window in the mask; depositing a further amount of a slurry including particles of the ceramic material onto the exposed portion of the further portion of the first portion of the sheet; Further comprising: The method of claim 14.

16. The slurry is deposited on the sheet by tape casting or screen printing. The method of claim 1.

17. The sheet having the plurality of thickness-wise openings is an electronically conductive sheet. The method of claim 1.

18. The sheet comprises a metal or a metal alloy.

20. The method of claim 17.

19. The sheet comprises iron or steel.

20. The method of claim 18.

20. The ceramic material is an electrode active material, and the amount of a solid electronically conductive component in the slurry is less than 10 vol% based on the total volume of the particles of the electrode active material.

20. The method of claim 17.

21. The particles of the ceramic material have a D50 particle size in the range of 10 nm to 50 μm. The method of claim 1.

22. The sheet is provided by a woven mesh. The method of claim 1.

23. The woven mesh has 5-500 strands per cm, measured perpendicular to the strands.

23. The method of claim 22.

24. The opening has a width in the range of 10-1000 μm. The method of claim 1.

25. 1. A method of manufacturing a battery cell, comprising:

2. Manufacturing a component according to the method of claim 1, wherein the component is an electrode and the ceramic material is an electrode active material; Fixing the electrode to a substrate; depositing a further battery layer on said electrode; A method comprising:

26. The step of fixing the electrode to the substrate includes spot welding the electrode to the substrate.

26. The method of claim 25.

27. 1. A component for use in an energy storage or energy conversion device, comprising: Component obtained or obtainable by the method of claim 1.

28. The component is an electrode for a battery cell, such as a solid-state battery cell.

28. The component of claim 27.

29. A component for use in an energy storage or energy conversion device, comprising: the component includes a first portion and a second portion, the first portion including particles of a ceramic material and the second portion being provided by a sheet having a plurality of through-thickness openings; the second portion is at least partially embedded in the first portion. Component.

30. The component is an electrode for a battery cell, such as a solid-state battery cell, and the ceramic material is an electrode active material.

30. The component of claim 29.

31. the first portion includes an ionically conductive component distributed between particles of the electrode active material; The ion-conductive component is 10 ?10 S.C.M. ?1 have a greater ionic conductivity and a melting point of 900° C. or less; 31. The component of claim 30.

32. The ionically conductive component contains lithium, boron, and optionally carbon as constituent elements.

32. The component of claim 31.

33. The ion conductive component is Li 3 B.O. 3 and Li 3?x B 1?x C x O 3 where 0<x<1; 33. The component of claim 32.

34. The second part is made of iron or steel (including stainless steel).

2. The component of claim 1.

35. The component has a first surface and a second surface opposite the first surface; the second portion is aligned with the first surface, and the distance of the second portion from the first surface is between 33% and 66% of a thickness of the component.

30. The component of claim 29.

36. the component has a first surface and a second surface opposite the first surface; the sheet includes a first portion, a second portion, and a connecting portion connecting the first portion and the second portion; the first portion and the second portion are aligned with the first surface and are at different distances from the first surface; 30. The component of claim 29.

37. the sheet comprises a third portion and a further connecting portion connecting the second portion and the third portion; the third portion is aligned with the first surface and offset from the first portion and the second portion; 37. The component of claim 36.

38. a mass per unit area of ​​the connecting portion of the sheet is smaller than a mass per unit area of ​​the first portion of the sheet; 37. The component of claim 36.

39. the connecting portion of the sheet includes at least one thicknesswise opening that encompasses an area greater than each of the thicknesswise openings of the first portion of the sheet; Component according to claim 38.

40. 28. An energy storage or energy conversion device comprising a component according to claim 27.

41. The device is selected from the group consisting of a battery, a capacitor, a fuel cell (including solid oxide fuel cells and polymer electrolyte fuel cells), a photovoltaic device, a piezoelectric device, and a thermoelectric converter.

41. An energy storage or energy conversion device as claimed in claim 40.

42. A solid-state battery cell comprising the components of claim 27, the component is an electrode, and the solid-state battery cell further includes an electrolyte layer disposed on a surface of the electrode. Solid-state battery cells.